2019
DOI: 10.1109/access.2019.2898874
|View full text |Cite
|
Sign up to set email alerts
|

Weapon-Target Assignment for Multi-to-Multi Interception With Grouping Constraint

Abstract: This paper presents a weapon-target assignment (WTA) method for a multi-to-multi interception with fixed and adaptive grouping constraints. First, to get a better evaluation of the interception performance, the miss-distance under heading error, the time-to-go, and the line-of-sight rate are used to construct an interception probability function which considers the interception efficiency and the required energy. Second, to provide good engagement conditions for cooperative guidance in the case of multiple mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This paper takes the medium/close-range ground-to-air missiles as two types of weapons. The interception probability of guided missile is investigated in [26]- [28]. It can be concluded that the interception probability of ground-to-air missiles is related to the guidance accuracy and the consumed energy in the flight process.…”
Section: Interception Probability Of Weaponmentioning
confidence: 99%
“…This paper takes the medium/close-range ground-to-air missiles as two types of weapons. The interception probability of guided missile is investigated in [26]- [28]. It can be concluded that the interception probability of ground-to-air missiles is related to the guidance accuracy and the consumed energy in the flight process.…”
Section: Interception Probability Of Weaponmentioning
confidence: 99%
“…In the present research work, the cylinder model with an infinite height is used to represent the no-fly zone. (22) where matrix C 2 = diag(0, 0, 0, 1, 1, 0) is used to extract the horizontal position of the members, N n is the number of the no-fly zones, and p nfz,l and R n,l are the horizontal position and the radius of the l th no-fly zone, respectively.…”
Section: ) Cooperative Constraintsmentioning
confidence: 99%
“…Very few studies on cooperative trajectory planning with free flight time exist in the literature. Meanwhile, in the cooperative attack scenario, multiple missiles are required to attack the target simultaneously to utilize formation advantage with the purpose of striking the enemy defense system and the target [21], [22]. To address this issue and to ensure the flight time consensus, Wang et al proposed a decoupled cooperative trajectory planning approach for UAV formation, in which the decoupled sub-problems of trajectory optimization considering the constraint on time consensus for each member was solved with SCP [23].…”
Section: Introductionmentioning
confidence: 99%
“…Affected by dimensions and severe environments, it is difficult to apply advanced navigation means, including high-precision inertial components like fiber-optic gyroscopes and image matching, in guided ammunition [6]. Due advantages such as its small size, anti-high overload capacity, strong autonomy, and high reliability, an inertial measurement system based on micro-electro-mechanical system-based inertial components has become an essential navigation component in the guidance process of rotating ammunition with high overload, high impact and short flight time [7][8][9]. However, because of its manufacturing technique, its measurement range and precision are not matched with each other; thus, the attitude of the ammunition when rotating at a high speed cannot be accurately measured by a traditional strapdown inertial navigation system [10].…”
Section: Introductionmentioning
confidence: 99%